Pengereman Motor Arus Searah (DC) Berbasis Mikrokontroller Atmega8535 - Yogie Novriandi; Noveri Lisbetty M; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Automatically braking the DC machine needs to be done given the enormous losses suffered due to motor overload. The use of a microcontroller in a series of motor braking is needed for braking the motor automatically has advantages such as precise, fast, and costeffective. It because the excess is then required circuit automatically controlling braking motorsusing microcontroller ATMega8535.Keywords : DC Machine, Braking, Microcontroller, Direct Current